In situ AFM studies of metal deposition - Hyde, M; Jacobs, R; Compton, R (2002)
In-situ AFM has been used to directly study the growth of individual lead nuclei on a highly boron doped diamond electrode and the rates at which they appear as a function of time and overpotential. This method represents a new approach to the study of these processes, previously only possible indirectly via comparison of potentiostatic current transients with models such as that of Scharifker and Mostany (Journal of Electroanalytical Chemistry, 1984, 177, 13). It therefore allows the assumptions made by these models to be tested in an independent manner. At high overpotentials, it is found that the growth rate of the nuclei is close to that predicted assuming diffusion control, a result representing the first direct verification that this is in fact the case using a method independent of current transient analysis. A re-expression for the Scharifker and Mostany equation for the current density, an improvement in that it allows less equivocal interpretation of the results, is suggested, and the nucleation rate derived from it compared with that determined directly by AFM. A very good agreement is found, demonstrating the validity of the in-situ AFM approach in this case, and also suggesting that the assumptions made by the Scharifker and Mostany model are substantially correct.